2015
DOI: 10.1093/jat/bkv010
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Sulfur Mustard Exposure in Human Plasma by LC-ESI-MS-MS Detection of the Albumin-Derived Alkylated HETE-CP Dipeptide and Chromatographic Investigation of Its Cis/Trans Isomerism

Abstract: Sulfur mustard (SM) is a chemical warfare agent that causes painful blisters and chemically modifies endogenous biomacromolecules by alkylation to hydroxyethylthioethyl (HETE) adducts representing valuable long-term markers for post-exposure analysis. The albumin adduct formed in human plasma in vitro (HETE bound to the side chain of cysteine 34) was isolated and cleaved by current lots of pronase primarily generating the internal modified dipeptide (HETE-cysteine-proline, HETE-CP) instead of the formerly repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
60
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 20 publications
4
60
0
1
Order By: Relevance
“…These peptides documented their suitability as biomarkers in plenty of studies [16][17][18][19][20][21][22][23] and thus represent highly valuable markers for SM exposure. After proteolysis with pronase and ProtK the alkylated peptides HETE-CP and HETE-CPF are generated, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…These peptides documented their suitability as biomarkers in plenty of studies [16][17][18][19][20][21][22][23] and thus represent highly valuable markers for SM exposure. After proteolysis with pronase and ProtK the alkylated peptides HETE-CP and HETE-CPF are generated, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, toxicity of SM is assumed to be due to the alkylation of proteins and DNA resulting in the functional impairment of cells, tissues, organs, and physiological processes. 12,[17][18][19][20][21][22][23] Based on the proteolysis of alkylated HSA, several analytical methods targeting the Cys 34 modification as HETE-CysProPhe (HETE-CPF) and HETE-CysPro (HETE-CP) were developed and have proven to be reliable biomarkers of exposure in vitro, in vivo, and in real cases of SM poisoning. 2 For the verification of an alleged use of SM, protein adducts reveal beneficial long-term stability of several weeks or even months in vivo when compared to products of SM hydrolysis and enzymatic biotransformation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that certain tyrosine residues are prone to phosphylation (denominating both phosphorylation and phosphonylation) by numerous OP and that Cys 34 – the only amino acid containing a free thiol group – can easily be modified by electrophiles (e.g. by alkylation with sulfur mustard) . Subsequent enzymatic cleavage of HSA allows generation of small cleavage products, which are analyzed using liquid chromatography/electrospray ionization tandem mass spectrometry (LC/ESI‐MS/MS).…”
mentioning
confidence: 99%
“…While phosphylation is the critical step of AChE inhibition by modification of its active site serine residue, we have recently shown that the corresponding leaving group of VX (2-(diisopropylamino)ethanethiol, DPAET) is also capable of forming adducts with endogenous cysteine residues of HSA [25] . Cys-Pro dipeptides including the only free cysteine sidechain at position 34 (C 34 P) were already known to result from pronase cleavage of HSA and facilitated the identification of DPAET-CP as a novel biomarker for VX exposure in vitro [8,[14][15][16][17]25] . Enzymatic cleavage of HSA incubated with VX using pronase resulted in cysteine and proline containing small peptides.…”
Section: Resultsmentioning
confidence: 99%